The Influence of Professional Ethics and Government Accounting Standards on the Quality of Financial Reporting in Gorontalo Regency - Dahu, Marlina Ak.; Abdullah, Julie; Saprudin; Junus, Onong; Hasan, Wahyudin (Future Science, 2025)
This study aims to analyze the influence of professional ethics and government accounting standards on the quality of financial reports in Gorontalo Regency. The research employs a regression model. The results show that both professional ethics and government accounting standards collectively have a significant impact on the quality of financial reports. Partial tests also indicate that each independent variable has a positive and significant effect on the quality of financial reports. The determination test (R2) results indicate that professional ethics and government accounting standards can explain approximately 64% of the variation. In conclusion, the application of good professional ethics and appropriate government accounting standards plays an important role in enhancing accountability and transparency in public financial management.